Digital hydraulics and "Industrie 4.0". (February 2017) - Brandstetter, Reinhard; Deubel, Till; Scheidl, Rudolf; Winkler, Bernd; Zeman, Klaus
This article addresses mainly questions about the roles of fluid systems, in particular of digital ones, in an "Industrie 4.0 (I4.0)" environment. There are three roles: the general machines' subsystems/components' role in machines of an I4.0 production system, the role of subsystems/components of machines which are produced under I4.0 conditions, and the manufacturing of fluid systems' components in an I4.0 setting. These roles are discussed and examples of digital hydraulic solutions which fulfill these roles excellently are presented. They feature simplicity and robustness of hardware components and transfer of functionality to software. It is concluded that components and subsystems can support the successful realization of I4.0-type production systems decisively.